Pemberdayaan Perempuan melalui Diversifikasi Produk Ikan menjadi Bakso dalam Upaya Pemenuhan Gizi dan Peningkatan Ekonomi Keluarga di Negeri Hulaliu - Mainassy, Meillisa Carlen; Delvis Kapelle, Imanuel Berly; Gainau, Paskanova Christi; Birahy, Deford Cristy; Baharudin, Indah; Waas, Alsye (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The women empowerment program in Negeri Hulaliu aims to improve nutritional fulfillment and family economic welfare through diversification of fish products into meatballs. This activity was carried out as a response to the high potential of fish resources but the low utilization of processed fish products. In this program, mothers are trained to process fish into meatballs that are nutritious and have economic value compared to fresh fish. The methods used include participatory approach, technical training on fish processing, mentoring, evaluation and monitoring. The results of this program showed an increase in participants' skills in processing fish and family economic income through the sale of fish balls. In addition, this program also contributes to the increased consumption of animal protein, which indirectly supports the improvement of family nutrition and economy. Thus, diversification of fish products into meatballs is expected to be one of the solutions in improving nutritional and economic intake in Negeri Hulaliu.